Relationship Between Incentives and Work Environment with Work Performance in The Improvement of The Company's Business - Nafi Almuzani; Teguh Purnomo (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
The study looked at the impact of work performance awards in improving a company's business development on incentives provided with the work environment. The goal is to determine the balance of performance assessment with the company's objectives so that it can take strategic decisions in business development through its employees. Observations are conducted using statistical tests that focus between incentives with work performance, work environment and work performance as well as incentives and work environments. Statistical testing is done to find out positive and significant relationships between variables in their interrelationships. Testing uses regression analysis, correlation, determination, correlation hypothesis. Observations find positive and significant values between variables. Indications of business development towards the achievement of targets will be greatly influenced by the variable factors tested so that it is found that staffing management has a large influence and benchmark on business development, especially limited liability companies